The extreme colliding-wind system Apep: resolved imagery of the central binary and dust plume in the infrared. Issue 4 (12th October 2020) - Han, Y; Tuthill, P G; Lau, R M; Soulain, A; Callingham, J R; Williams, P M; Crowther, P A; Pope, B J S; Marcote, B
ABSTRACT: The recent discovery of a spectacular dust plume in the system 2XMM J160050.7–514245 (referred to as 'Apep') suggested a physical origin in a colliding-wind binary by way of the 'Pinwheel' mechanism. Observational data pointed to a hierarchical triple-star system, however, several extreme and unexpected physical properties seem to defy the established physics of such objects. Most notably, a stark discrepancy was found in the observed outflow speed of the gas as measured spectroscopically in the line-of-sight direction compared to the proper motion expansion of the dust in the sky plane. This enigmatic behaviour arises at the wind base within the central Wolf–Rayet binary: a system that has so far remained spatially unresolved. Here, we present an updated proper motion study deriving the expansion speed of Apep's dust plume over a 2-year baseline that is four times slower than the spectroscopic wind speed, confirming and strengthening the previous finding. We also present the results from high angular resolution near-infrared imaging studies of the heart of the system, revealing a close binary with properties matching a Wolf–Rayet colliding-wind system. Based on these new observational constraints, an improved geometric model is presented yielding a close match to the data, constraining the orbital parameters of the Wolf–Rayet binary and lending further support to the anisotropic wind model.